2007
DOI: 10.1128/jvi.00106-07
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Human Monoclonal Antibody to Human Metapneumovirus Fusion Protein That Neutralizes Virus In Vitro and Is Effective Therapeutically In Vivo

Abstract: Human metapneumovirus (hMPV) is a recently discovered paramyxovirus that is a major cause of lowerrespiratory-tract disease. hMPV is associated with more severe disease in infants and persons with underlying medical conditions. Animal studies have shown that the hMPV fusion (F) protein alone is capable of inducing protective immunity. Here, we report the use of phage display technology to generate a fully human monoclonal antibody fragment (Fab) with biological activity against hMPV. Phage antibody libraries p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 90 publications
7
62
0
1
Order By: Relevance
“…This result is in concordance with the findings of Levy et al (10), which showed that vaccinating mice with HMPV F/G VLPs elicited cross-protective antibodies, and with other reports showing that passive antibody transfer protects mice from HMPV infection (71,72). Furthermore, given that the F and M proteins of one HMPV subtype share high amino acid sequence homology with those of different HMPV subtypes, there may also be shared T CD8 epitopes between the different subtypes that contribute to heterosubtypic immunity.…”
Section: Discussionsupporting
confidence: 83%
“…This result is in concordance with the findings of Levy et al (10), which showed that vaccinating mice with HMPV F/G VLPs elicited cross-protective antibodies, and with other reports showing that passive antibody transfer protects mice from HMPV infection (71,72). Furthermore, given that the F and M proteins of one HMPV subtype share high amino acid sequence homology with those of different HMPV subtypes, there may also be shared T CD8 epitopes between the different subtypes that contribute to heterosubtypic immunity.…”
Section: Discussionsupporting
confidence: 83%
“…Our data suggest that the hMPV-specific antibody response may contribute to protection against or reduction of the severity of the illness. This hypothesis is in accordance with the results from Alvarez and Tripp (2), who showed that the passive transfer of hMPV-immune serum protected naïve BALB/c mice to a certain degree from challenge, and with the results from Williams et al (57), who reported that a neutralizing monoclonal antibody to the F protein conferred protection against challenge (2, 57). Whole-body plethysmography has been used to assess whether acute hMPV infection results in increased AO.…”
Section: Discussionsupporting
confidence: 81%
“…This may occur because of limited cross-protective immunity between different strains of HMPV or may indicate that antibody-mediated protection is not sufficient to prevent HMPV infection. However, studies with animal models indicate that passive transfer of anti-HMPV neutralizing antibodies can protect against HMPV replication and disease (45,46,63). Furthermore, in otherwise healthy adults, HMPV infection is typically limited to the upper respiratory tract, suggesting that neutralizing antibodies can ameliorate HMPV disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Only the F protein is required for virus assembly, fusion, and entry (13,44). Furthermore, the HMPV F protein is the primary target of neutralizing antibodies (13,23,(45)(46)(47)(48). In contrast, while HMPV G is immunogenic in rodents, G-specific antibodies do not neutralize HMPV and G vaccines provide no protection in animals (47)(48)(49).…”
mentioning
confidence: 99%